SOME FEATURES IN INTERACTIONS BETWEEN SYMBIONTS AND THEIR HOSTS AS EXEMPLIFIED BY STARFISH CULCITA NOVAEGUINEAE AND GASTROPODS STILIFER VARIABILIS - Polina Dgebuadze (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2018)
During the observations of echinoderms in the natural conditions (South China Sea, Nha Trang Bay), a peculiar phenomenon of the rejection of symbiotic gastropods by host-starfish tissues was discovered. Later on, laboratory experiments were carried out in aquariums in order to find the cause of this phenomenon. Starfish Culcita novaeguineae bearing gastropods Stilifer variabilis were kept for 10 days in aquariums with no aeration and a gradual increase in water temperature. as a result, an unusual behavior of gallforming symbiotic gastropods was revealed: the apex of the shell began to stick more out of the surface of the host’s body, and in some cases sudden ejection of egg capsules by the symbionts was noted. In contract to the natural conditions, however, the symbionts neither died nor were totally rejected by the host’s tissues. There are plans to continue aquarium-based laboratory experiments with a larger selection of starfish and their symbionts, and to analyze various abiotic environmental factors (not only the temperature regime and the oxygen content in the water).